Geometrical Properties of Skeletal Structures of Radiolarian Genus Didymocyrtis - Yoshino, Takashi; Matsuoka, Atsushi; Kishimoto, Naoko (Image Analysis and Stereology, 2019)
This paper discusses the geometrical properties of a radiolarian skeletal structure, namely, that of genus Didymocyrtis. We characterized the evolution of skeletal structures and analyzed the structures using geometry. We defined two ratios in order to quantify the geometrical properties of Didymocyrtis and verified that the two ratios changed with their phylogenic evolution. We also used the 3D skeletal data of a specimen of species D. tetrathalamus, which were obtained through micro X-ray CT. The cortical shell obtained in the 3D data was projected onto a spherical surface, and we determined the centers of the pores. Our analysis revealed that the number of pores is approximately 200 and their distribution is not regular. We also determined that the column-like parts of the skeleton, which connect the inner and upper parts of the specimen, do not lie on a plane and their intervals are not equal.